Analysis Productivity Labor in Indonesia - Fildjah Najibah Ghaisani; Indri Arrafi Juliannisa; M. Faizhal Ghaisani (Equity: Jurnal Ekonomi, 2025)
In the ASEAN context, the Republic of Indonesia ranks fourth in labor productivity within the region, reflecting ongoing complex challenges in optimizing its labor sector. Despite being endowed with abundant labor resources, Indonesia’s labor productivity lags behind several ASEAN neighbors, influenced by factors such as education gaps, skills mismatches, and uneven regional development. This study aims to identify Indonesian provinces falling into the optimal category of labor productivity based on key criteria: Gender Development Index, Health, Minimum Wage, and Investment. The novelty lies in explaining how Indonesia's regional characteristics form diverse pathways that illustrate the optimization potential of these regions. The objective of this study focuses on examining the conditions of regional characteristics associated with optimal labor productivity. This research uses a continuous analysis method known as Crisp-set Qualitative Comparative Analysis (csQCA). csQCA specializes in analyzing binary data to identify multiple causal patterns logically and holistically. It uses Boolean algebra to simplify complex data sets, revealing how different combinations of conditions relate to outcomes. The objects studied were 34 provinces in Indonesia in 2023. The results showed that provinces with optimal Gender Development Index conditions are located in the DKI Jakarta area with the flagship Transjakarta Pink program. In addition, the optimal Good Health Operational (BOK) conditions are in the Southeast Sulawesi region through the flagship program of the Mobile Health Service Program. Optimal wage conditions were observed in 19 provinces as a result of government policies in maintaining people's purchasing power.